An assessment of general road illumination system simulation methods and comparison of simulation outcomes with photometric measurements conducted on a public road with anthropogenic sources of peripheral illumination - Ayaz, Ramazan; Roy, Subarna; Bhattacharya, Sourin (SPRINGER INDIA, 2024)
Implementation of controllable, reliable, and energy-efficient lighting systems for roads and thoroughfares is a public necessity and the use of software simulation in road lighting design can provide contractors and project engineers with a comprehensive view of the deliverables in road illumination projects. In this study, three different methods used to simulate road illumination systems are expounded: a general-purpose road lighting simulation program, a proprietary industry-standard simulation software, and a multiple regression-based road lighting model. Then, simulations are conducted for twelve ideal geometrical design configurations with the three methods and the outputs are compared. Furthermore, field measurements are made with a luminance camera on a public road utilizing induction luminaires in Turkey and simulations are conducted for comparison. It is found that simulated average luminance values are about 31.80-33.23% lower than those under field testing conditions and overall uniformity of luminance and longitudinal uniformity of luminance differ considerably as well. Such disparities can be primarily ascribed to partial interreflection of luminous flux and anthropogenic spill light from the adjacent establishments. Therefore, for congruence, it is imperative to consider the potential contributions of peripheral light sources in the simulation models and methods of road illumination systems.
Keywords: Road lighting simulation; Peripheral illumination; Artificial light at night; Induction lamp; Light pollution; Luminance measurement; ENERGY EFFICIENCY; LIGHTING QUALITY; LED LUMINAIRES; HPS LUMINAIRES; DESIGN; OPTIMIZATION; POLLUTION; Optics